Variations in the perception of the elements that constitute training based on company size, employee seniority, and company age = Odchylenia w postrzeganiu elementów składających się na szkolenie w oparciu o wielkość firmy, staż pracowników i wiek firmy - Vásquez-Torres, Maria del Carmen (Zielona Góra: Faculty of Economics and Management Press)
The implementation of training programs in industrial enterprises is determined by the elements that constitute training and variations in the perception of and value placed on those elements. This study aims to present an analysis of the variations in the per-size, management position seniority, and company age. For the analysis, we used one-way ANOVA to quantify the differences and post-hoc Bonferroni tests to assign values to the differences.
Keywords: szkolenia; programy szkoleniowe; analiza zmian; przedsiębiorstwo przemysłowe; wielkość firmy; training; seniority; permanence; company size